PENGARUH TURNOVER INTENTION DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PT. RAJAWALI II UNIT PG JATITUJUH DI MAJALENGKA - Windy Sari, - (2023)
This study aims to determine the Effect of Turnover Intention and Work Stress on Employee Performance. The type of research used is descriptive verification, namely by describing and explaining the variables studied and then drawing conclusions. The variables in this study are the independent variable (X1) Turnover Intention, (X2) Work Stress, and the dependent variable (Y) Employee Performance. The population in this study are employees of PT. Rajawali II Unit PG Jatitujuh Majalengka. Sampling in this study used the probability sampling method with saturated sampling of 94 employees of PT. Rajawali II Unit PG Jatitujuh Majalengka. The instrument test was carried out by testing the validity and reliability tests and the technique used was multiple regression analysis with SPSS 22.0 for windows computer software. The findings of this study indicate that the description of turnover intention and work stress on the performance of PT. Rajawali II Unit PG Jatitujuh Majalengka is in the good category. turnover intention and work stress have a positive and significant impact on the performance of employees of PT. Rajawali II Unit PG Jatitujuh Majalengka.